β-glucan: a potent adjuvant in immunotherapy for digestive tract tumors - Wang, Meiyu; Pan, Jinhua; Xiang, Wu; You, Zilong; Zhang, Yue; Wang, Junyu; Zhang, Anren (Frontiers in Immunology, 2024)
The immunotherapy for gastrointestinal tumors, as a significant research direction in the field of oncology treatment in recent years, has garnered extensive attention due to its potential therapeutic efficacy and promising clinical application prospects.Recent advances in immunotherapy notwithstanding, challenges persist, such as side effects, the complexity of the tumor immune microenvironment, variable patient responses, and drug resistance. Consequently, there is a pressing need to explore novel adjunctive therapeutic modalities. β-glucan, an immunomodulatory agent, has exhibited promising anti-tumor efficacy in preclinical studies involving colorectal cancer, pancreatic cancer, and gastric cancer, while also mitigating the adverse reactions associated with chemotherapy and enhancing patients' quality of life. However, further clinical and fundamental research is warranted to comprehensively evaluate its therapeutic potential and underlying biological mechanisms. In the future, β-glucan holds promise as an adjunctive treatment for gastrointestinal tumors, potentially bringing significant benefits to patients.